Designing Information Acquisition Tools for Assessing the Status of Outpatient Training for Medical Students - Ali Hamzezadeh; Saeideh Ghaffarifar; Abolghasem Amini (مجله ایرانی آموزش در علوم پزشکی, 2019)
Introduction: Outpatient medical education is one of the important parts of clinical training in medical education which has been given particular attention today due to its deep relationship with the future of the physician's occupation. Lack of proper tools and standards for assessing the status of outpatient education is one of the obstacles to conducting ambulatory education assessment studies. Therefore, this study was aimed at developing instruments for assessing outpatient training of medical students during externship and internship in Clinics Affiliated to the Medical Sciences Universities. Methods: This developmental and psychometric study was conducted to develop an outpatient education assessment instrument in educational clinics. The sources used were included reputable medical education reference books, general medical education curriculum and previous studies. For standardization and calculation of reliability and validity, Cronbach's alpha coefficient and survey of specialists were used respectively. We used SPSS tools for data processing, and Pearson correlation index for inferential analysis. Results: The developed instruments included two educational status assessment questionnaires from the viewpoint of students (reliability 89%, validity 85%) and faculty members (reliability 90%,validity 85%), a patient satisfaction assessment questionnaire (reliability 90%,validity 80%), and an observational checklist for assessment of educational clinics (reliability 95%,validity 82%). Conclusion: The developed instruments in this study compared with the instruments used in previous studies simultaneously evaluates the status of outpatient education from the viewpoint of all the three involved exposures, including tutor, learner, and patient; which is the important positive point. The evaluation of educational clinics of medical universities in the future with the developed instruments in this study while providing a clear image of the status, can provide comparable information between educational centers.